Work-family conflict, social support, psychological well-being, dan emotional fatigue pada wanita pekerja - Riski, Nadia; Ticoalu, Yurice Betrix (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study examines the impact of work-family conflict, social support, psychological well-being, and emotional fatigue among female workers based on a review of previous literature. The analysis reveals that work-family conflict experienced by female workers can lead to decreased workplace performance and quality of family interactions. However, high social support can help reduce emotional fatigue and increase life satisfaction among female workers. Moreover, high psychological well-being can be achieved with full support from the surrounding environment, while emotional fatigue can be alleviated through increased social support and effective conflict management between work and family. In conclusion, it is important for companies and families to provide adequate support to female workers to address work-family conflict and enhance their overall well-being.